Cerebral blood flow, frontal lobe oxygenation and intra-arterial blood pressure during sprint exercise in normoxia and severe acute hypoxia in humans. Issue 1 (January 2018) - Curtelin, David; Morales-Alamo, David; Torres-Peralta, Rafael; Rasmussen, Peter; Martin-Rincon, Marcos; Perez-Valera, Mario; Siebenmann, Christoph; Pérez-Suárez, Ismael; Cherouveim, Evgenia; Sheel, A William; Lundby, Carsten; Calbet, José AL
Cerebral blood flow (CBF) is regulated to secure brain O2 delivery while simultaneously avoiding hyperperfusion; however, both requisites may conflict during sprint exercise. To determine whether brain O2 delivery or CBF is prioritized, young men performed sprint exercise in normoxia and hypoxia (PI O2 = 73 mmHg). During the sprints, cardiac output increased to ∼22 L min −1, mean arterial pressure to ∼131 mmHg and peak systolic blood pressure ranged between 200 and 304 mmHg. Middle-cerebral artery velocity (MCAv) increased to peak values (∼16%) after 7.5 s and decreased to pre-exercise values towards the end of the sprint. When the sprints in normoxia were preceded by a reduced PET CO2, CBF and frontal lobe oxygenation decreased in parallel ( r = 0.93, P < 0.01). In hypoxia, MCAv was increased by 25%, due to a 26% greater vascular conductance, despite 4–6 mmHg lower PaCO2 in hypoxia than normoxia. This vasodilation fully accounted for the 22 % lower CaO2 in hypoxia, leading to a similar brain O2 delivery during the sprints regardless of PI O2 . In conclusion, when a conflict exists between preserving brain O2 delivery or restraining CBF to avoid potential damage by an elevated perfusion pressure, the priority is given to brain O2 delivery.